2021
DOI: 10.1128/jcm.00388-21
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of the Abbott Alinity SARS-CoV-2 Spike-Specific Quantitative IgG and IgM Assays among Infected, Recovered, and Vaccinated Groups

Abstract: The COVID-19 pandemic continues to impose a significant burden on global health infrastructure. While identification and containment of new cases remains important, laboratories must now pivot and consider an assessment of SARS-CoV-2 immunity in the setting of the recent availability of multiple COVID-19 vaccines. Here we have utilized the latest Abbott Alinity semi-quantitative IgM and quantitative IgG spike protein (SP) serology assays (IgMSP and IgGSP) in combination with Abbott Alinity IgG nucleocapsid (NC… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
85
1
10

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(107 citation statements)
references
References 18 publications
11
85
1
10
Order By: Relevance
“…Two Index values of ≥1.4 (IgG NC ), ≥1.0 (IgM SP ), and ≥50 AU/mL (IgG SP ) were interpreted as positive per the manufacturer’s recommended threshold. IgG NC positivity informs natural SARS-CoV-2 infection, while IgG SP /IgM SP positivity strongly correlates with the emergence of natural or vaccine-driven neutralizing immunity [ 5 , 7 ]. CD4+ T-cell activity was assessed as a marker of immune competence using the ImmuKnow ® assay (Viracor-IBT, Lee’s Summit, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two Index values of ≥1.4 (IgG NC ), ≥1.0 (IgM SP ), and ≥50 AU/mL (IgG SP ) were interpreted as positive per the manufacturer’s recommended threshold. IgG NC positivity informs natural SARS-CoV-2 infection, while IgG SP /IgM SP positivity strongly correlates with the emergence of natural or vaccine-driven neutralizing immunity [ 5 , 7 ]. CD4+ T-cell activity was assessed as a marker of immune competence using the ImmuKnow ® assay (Viracor-IBT, Lee’s Summit, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
“…We and others have demonstrated that the serological assessment of IgG and IgM against SARS-CoV-2 nucleocapsid (NC) and spike (SP) proteins is reliable in differentiating humoral responses to infection versus vaccination [ 2 , 3 , 4 , 5 , 6 ]. A recent study has evaluated a conservative IgG Spike-Receptor Binding Domain (S-RBD) level (Abbott assay) as a surrogate measure of antibody neutralization and identified that at or above 4160 AU/mL, the IgG (S-RBD) titer estimates consistently corresponded to a 0.95 probability of the plaque reduction neutralization test (PRNT; the gold standard) proportion at a 50-stringency threshold for 1/250 dilution.…”
Section: Introductionmentioning
confidence: 99%
“…The protein has several epitopes that stimulate B and T cell responses and are suitable for vaccine formulations [10]. Moreover, as most SAR-CoV-2 vaccines used in humans are based on the spike antigen, the detection of antibody responses against nucleocapsid protein may be useful for distinguishing between serologic responses to infection and vaccination [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, a serological study revealed 39 391.2 AU/mL of anti-S IgG 17 days after the positive PCR test (30 days after complete vaccination), a value significantly higher than that of most SOT recipients (36 of 37) but comparable with those of fully vaccinated immunocompetent or previously infected control groups ( Fig. 1 ) ( 4 ). This finding indicates that subsequent infection may function as an additional stimulus to boost antibody response and induce higher levels of anti-S IgG in SOT recipients.…”
mentioning
confidence: 87%
“…The seroconversion rate of SOT recipients (40.5%) was significantly lower than the 100% positive antibody response in fully vaccinated immunocompetent individuals and patients with past COVID-19 infection ( Fig. 1 ) ( 4 ). In addition, the median value of anti-S IgG in SOT recipients (1.4 AU/mL) was approximately 10 000-fold lower than median values observed in vaccinated immunocompetent individuals (13 951.5 AU/mL) and patients with past infection (16 532.5 AU/mL) ( t -test; P < 0.005) ( Fig.…”
mentioning
confidence: 89%